KPIs Implementation in International Company - Jungwirth, Lubomír (2013)
This thesis deals with the concept of corporate performance management. The main goal is to present the main aspects of business performance and prosperity and according to this find the way to prosperity. The work is divided into several parts. The first part is focused on the theoretical basis of business management prosperity. The second part deals with the concept of performance management. The third part deals with the forecasting function. The last part is the application of theoretical knowledge from previous sections. Unfortunately, the area of corporate performance management and business prosperity is so broad and the scope of this thesis is limited. This applies to the methods that can be used. Emphasis was placed on the most used methods. The thesis should provide a comprehensive view on this issue.